Integrasi Media Sosial dalam Pembelajaran Pendidikan Agama Islam: Studi Kasus Pemanfaatan TikTok sebagai Media Dakwah di Kalangan Santri - Abdurrahman Nasution; Sahnila Sari Hasibuan (Yayasan Salam Cerdas Al-Fattah, 2025)
The development of digital technology has transformed patterns of communication and learning, including in the field of Islamic religious education. Social media platforms such as TikTok, which were initially used for entertainment purposes, have now evolved into new spaces for religious preaching (dakwah) and Islamic learning activities. This phenomenon requires santri (Islamic boarding school students) to adapt and integrate dakwah with digital media in creative and effective ways. This study aims to analyze how santri utilize TikTok as a medium for digital dakwah and to examine its implications for Islamic Religious Education learning in the social media era. This research employs a qualitative approach with a case study method, conducted in an Islamic boarding school actively using TikTok as a platform for dakwah. Data were collected through in-depth interviews, observation of santri’s dakwah activities on TikTok, and documentation of digital content. The collected data were analyzed descriptively through the stages of data reduction, data display, and conclusion drawing to identify thematic patterns relevant to the focus of the study. The findings reveal that santri utilize TikTok to disseminate dakwah messages creatively by using simple language, appealing visuals, and short durations to suit the characteristics of young audiences. The main motivation of santri in conducting dakwah through TikTok is to widely spread Islamic values and to adapt the methods of dakwah to technological developments. The audience’s response to the dakwah content is generally positive, although challenges remain, such as limited duration, competition with entertainment content, and the risk of message misinterpretation. The study concludes that the use of TikTok by santri represents a tangible form of integration between social media and Islamic Religious Education learning. Digital dakwah not only expands the reach of Islamic values but also enhances santri’s media literacy, creativity, and communication skills. The implication is that Islamic educational institutions need to adjust their learning strategies to be more adaptive to digital technological developments without neglecting spiritual values and the ethical principles of dakwah in Islam.